OPTIMIZING EMPLOYEE EXPERTISE IN MANAGING INVENTORY OF BMD INTEGRATED SPECIAL SCHOOL (SLB) (Case Study at the Education and Culture Office of Central Papua Province) - Yuli Yasmin Tecuari; Baharuddin; Corvis L Rantererung (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to analyze the Optimization of Employee Expertise in Integrated Management of Special School (SLB) BMD Inventory (Case Study in the Education and Culture Office of Central Papua Province). This study uses a qualitative descriptive approach. Data sources are from primary and secondary data. Data collection methods: observation, interviews with informants and documentation. Informants in this study were 5 (five) employees. The data analysis method uses a qualitative descriptive analysis method with the analysis stages: data reduction, data presentation and drawing conclusions. The results of this study indicate that: 1) The level of employee expertise in integrated Office Assets inventory management is still uneven, with many employees in the learning and adaptation stage. Interventions in the form of training, technical support, and infrastructure improvements are needed to accelerate employee capacity building in the era of digitalization of government asset administration. 2). Obstacles in integrated Office Assets inventory management at the Central Papua Province Education and Culture Office are multidimensional, covering aspects: technical, human resources, infrastructure, and managerial. 3). Optimizing Employee Expertise in Integrated Office Assets Inventory Management at the Central Papua Province Education and Culture Office, is carried out through a practice-based approach (learning by doing) and special assignments to employees with IT backgrounds as an effective strategy to accelerate mastery of the Office Assets Inventory system by employees.